Penggunaan Think-Aloud Protocol dan Usability Testing untuk Mengidentifikasi Masalah Usability pada Aplikasi E-Commerce Shopee - Siti Sabrina Ramadanti Abdul; Lillyan Hadjaratie; Huzaima Mas’ud; Roviana H Dai; Eka Vickraien Dangkua (Transbahasa, 2026)
The rapid growth of the e-commerce industry requires mobile applications to provide intuitive interfaces that support efficient and satisfying user interactions. Shopee, one of the largest e-commerce platforms in Indonesia, continues to receive user complaints regarding visual density, complex navigation, and excessive interface elements that may increase users' cognitive load. This study aims to evaluate the usability of the Shopee mobile application by employing a mixed-methods approach that combines quantitative and qualitative techniques. Quantitative data were collected using the System Usability Scale (SUS) questionnaire administered to 150 respondents, while qualitative insights were obtained through the Concurrent Think-Aloud (CTA) method involving 10 participants performing representative shopping tasks. The findings reveal an average SUS score of 73.18, indicating a Good usability rating with an Acceptable level of user acceptance. The relatively favorable score is strongly influenced by users' familiarity with the platform, reflecting learned behavior developed through repeated use. However, the qualitative findings identified several usability issues, including the absence of a search feature on the shopping cart page, visual distractions caused by autoplay mechanisms, inconsistent navigation flow, and a suboptimal hierarchy of product information. Based on these findings, this study recommends redesigning the interface hierarchy, minimizing unnecessary visual clutter, introducing contextual search functionality, and simplifying navigation to improve interaction efficiency and overall user experience.